(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Butyl stearate and polyurea resin polymerized via toluene-2, 4-diisocyanate (TDI) and diethylene triamine (DETA) were respectively used as the core material and the shell material in preparing MicroPCMs. The phase change properties, chemical structure, surface morphology and particle size and size distribution of microcapsules were investigated by using DSC, FTIR, SEM and Malvern laser particle size analyzer. The results show that the prepared MicroPCMs were smooth and compact. Their melting temperature and enthalpies were 23.3 °C and 79.7 J ⋅ g^-1 respectively. The average diameter of microencapsulated PCM (MicroPCMs) is in the range of 4.5 ˜ 10.2 μm under the stirring speed of 3000 ˜ 6000 rpm. Furthermore, a two-step method of adding DETA was firstly presented, through this method, the heat stability and ethanol wash stability of the MicroPCMs has been greatly improved, and the shell of MicroPCMs prepared by the two-step method has better stability and compactness than one-step method.